Removal of copper and lead ions from aqueous solutions by adsorbents derived from groundwater treatment sludge - Tumampos, Stephanie B. (College of Engineering, University of the Philippines Diliman, 2015)
Heavy metals such as Cu and Pb ions are present in varying concentrations in the effluents of electroplating factories. In this study, novel adsorbents synthesized from groundwater treatment sludge (GWTS) were used to remove Cu and Pb ions from contaminated solutions. The effects of pH and temperature during adsorbent synthesis on Cu and Pb uptake by the novel adsorbent were investigated. Metal adsorption followed the pseudo-second order kinetic equation for individual (R2>0.9834) and binary (R2>0.9742) metal systems. Activation energy was computed and found out to be 39.45 kJ mol-1 for Cu and 44.31 kj mol-1 for Pb. In addition, the Langmuir isotherm best describes the metal uptake of the adsorbent for individual(R2>0.9702) and binary (R2>0.9591) metal systems. Fourier transform infrared (FTIR) spectra of the adsorbents confirmed the presence of OH and Mn oxides. In addition, the adsorbent pH at point-of zero charge, particle size, morphology and surface composition were analyzed by the Drift method, particle size analyzer, scanning electron microscopy(SEM) and energy dispersive X-ray (EDX) analyses, respectively. The pHpzc Was determined to be at pH 6.0. The SEM results showed that the MnO2-GWTS had a different morphological structure than that of the MnO2 reagent, yet both have a 70-30 ratio of Mn and 0, respectively thru the EDX analysis. Particle sizes of MnO2-GWTSvaried from 220 nm and 5420 nm. Overall, the findings of this study demonstrates the potential of adsorbent derived from GWTS to remove metals from industrial effluents.